Vaccination-Induced Skin-Resident Memory Cd8+ T Cells Mediate Strong Protection Against Cutaneous Melanoma - Borgna-Christie, V (Taylor and Francis Inc., 2018)
Memory CD8+ T cell responses have the potential to mediate long-lasting protection against cancers. Resident memory CD8+ T (Trm) cells stably reside in non-lymphoid tissues and mediate superior innate and adaptive immunity against pathogens. Emerging evidence indicates that Trm cells develop in human solid cancers and play a key role in controlling tumor growth. However, the specific contribution of Trm cells to anti-tumor immunity is incompletely understood. Moreover, clinically applicable vaccination strategies that efficiently establish Trm cell responses remain largely unexplored and are expected to strongly protect against tumors. Here we demonstrated that a single intradermal administration of gene- or protein-based vaccines efficiently induces specific Trm cell responses against models of tumor-specific and self-antigens, which accumulated in vaccinated and distant non-vaccinated skin. Vaccination-induced Trm cells were largely resistant to in vivo intravascular staining and antibody-dependent depletion. Intradermal, but not intraperitoneal vaccination, generated memory precursors expressing skin-homing molecules in circulation and Trm cells in skin. Interestingly, vaccination-induced Trm cell responses strongly suppressed the growth of B16F10 melanoma, independently of circulating memory CD8+ T cells, and were able to infiltrate tumors. This work highlights the therapeutic potential of vaccination-induced Trm cell responses to achieve potent protection against skin malignancies. © 2018 The Author(s). Published with license by Taylor & Francis Group, LLC © 2018, © Felipe Gálvez-Cancino, Ernesto López, Evelyn Menares, Ximena Díaz, Camila Flores, Pablo Cáceres, Sofía Hidalgo, Ornella Chovar, Marcela Alcántara-Hernández, Vincenzo Borgna, Manuel Varas-Godoy, Flavio Salazar-Onfray, Juliana Idoyaga and Alvaro Lladser.